Critical factors governing vertical phase separation in polymer–PCBM blend films for organic solar cells. Issue 40 (23rd September 2016) - Kim, Min; Lee, Jaewon; Jo, Sae Byeok; Sin, Dong Hun; Ko, Hyomin; Lee, Hansol; Lee, Seung Goo; Cho, Kilwon
Abstract : This study presents an effective guide to vertical phase separation of polymer–fullerene blends based on systematic comparison of compatibility, crystallization, and processing conditions in observing the vertical morphology. Abstract : In organic bulk-heterojunction solar cells, the vertical distribution of the composition of the active layers as well as the lateral morphology is one of the critical issues that can significantly affect charge transport and recombination characteristics. Here we studied the critical parameters that can affect the formation of vertically stratified bulk heterojunction organic solar cells based on various polymers with different side chains, and investigated the effect of the miscibility of the polymer–fullerene blend and the crystallinity of the polymer on vertical morphology. The major factor that affected the vertical phase separation was the interaction parameter χ between the polymer and phenyl-C61 -butyric acid methyl ester (PCBM). Polymer–PCBM blends with high values of χ tended to trigger surface-directed vertical phase separation during rapid solvent evaporation. However, strong aggregation of polymers with low solubility counteracted this surface-directed vertical stratification. Moreover, solvent additives strongly affected the vertical phase separation processes, and caused the composition of the active layer to fluctuate dramatically. We also found the photovoltaic characteristics, including charge recombination time, to be strongly affected by the vertical distribution of the composition. The modulation of the composition in the vertical direction should therefore be optimized to increase the efficiency of charge collection and hence achieve high-efficiency organic solar cells.